Characterisation of taro (Colocasia esculenta) based on morphological and isozymic patterns markers - TRIMANTO TRIMANTO; SAJIDAN SAJIDAN; SUGIYARTO SUGIYARTO (Smujo International, 2011)
Abstract. Trimanto, Sajidan, Sugiyarto. 2011. Characterization of taro (Colocasia esculenta) based on morphological and isozymic patterns markers. Nusantara Bioscience: 7-14. The aims of this research were to find out: (i) the variety of Colocasia esculenta based on the morphological characteristics; (ii) the variety of C. esculenta based on the isozymic banding pattern; and (iii) the correlation of genetic distance based on the morphological characteristics and isozymic banding pattern. Survey research conducted in the Karanganyar district, which include high, medium and low altitude. The sample was taken using random purposive sampling technique, including 9 sampling points. The morphological data was elaborated descriptively and then made dendrogram. The data on isozymic banding pattern was analyzed quantitatively based on the presence or absence of bands appeared on the gel, and then made dendrogram. The correlation based on the morphological characteristics and isozymic banding pattern were analyzed based on the product-moment correlation coefficient with goodness of fit criterion. The result showed : (i) in Karanganyar was founded 10 variety of C. esculenta; (ii) morphological characteristics are not affected by altitude; (iii) isozymic banding pattern of peroxides forms 14 banding patterns, esterase forms 11 banding patterns and shikimic dehydrogenase forms 15 banding patterns; (iv) the correlation of morphological data and the isozymic banding pattern of peroxidase has good correlation (0.893542288) while esterase and shikimic dehydrogenase isozymes have very good correlation (0.917557716 and 0.9121985446); (v) isozymic banding pattern of data supports the morphological character data.